Identifying mechanisms behind crack formation and destruction of the damper winding of a capsule-type hydrogenerator in the presence of static rotor eccentricity - Geraskin, Olexandr; Haidenko, Yurii; Chumack, Vadim; Mihaylenko, Vladislav; Trotsenko, Yevhenii (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates a capsule-type SGK 538/160–70M hydrogenerator with a rated power of 23 MVA. The task addressed relates to crack initiation and failure of the damper winding in the hydrogenerator in the presence of rotor static eccentricity. A three-dimensional field-based mathematical model of the electromagnetic-thermal-mechanical interaction has been constructed to evaluate the distributions of currents, temperatures, and thermomechanical stresses in the damper winding segment and in the brazed joints of rods. It is shown that the occurrence and evolution of rotor static eccentricity constitute one of the essential causes of catastrophic damages and failures in hydrogenerators of this type. It has been determined that, under rotor static eccentricity of ε = 0.83, the local stresses in the joint of the central rod increase by a factor of 3.2 (up to ≈ 540 MPa). This value exceeds the tensile strength of copper and explains rod ruptures and avalanche-type failure of the segment. In addition, it was established that the existence and localization of cracks in brazed joints significantly affect the bending (deformation) behavior of the pole damper winding segment. The results could be applied to estimate the service life and to upgrade large slow-speed synchronous hydrogenerators (including capsule types). Specifically, under the following conditions: a) existing or expected eccentricities; b) high thermal gradients in the end/short-circuiting parts of the damper winding; c) operation with frequent starts/stops or cooling modes close to limiting values. The effective engineering measures that have been proposed, such as improving the mobility of rods in slots; revising the number and diameters of rods; applying high-strength materials, could be implemented in retrofitting projects and when repairing the rotor